Social capital, neighbourhood characteristics and utilisation of local public health services among domestic migrants in China: a cross-sectional study. Issue 8 (18th August 2017) - Hou, Zhiyuan; Lin, Senlin; Zhang, Donglan
Abstract : Objectives: We examined the association between structural social capital and public health services use, and explored the modifiable effect of neighbourhood factors on this association among domestic migrants in China. Methods: Data were from a 2014 nationally representative cross-sectional sample of domestic migrants aged 15–59 years in China. Survey-weighted logistic regression models were applied to assess the association between structural social capital, measured by participation in social organisations and social activities, and use of public health services. Interaction terms between neighbourhood urban status, neighbourhood composition and social capital were further assessed in the models. Results: Migrants who participated in social organisations were more likely to establish health records (OR 1.467, 95% CI 1.201 to 1.793) and receive health education information (OR 1.729, 95% CI 1.484 to 2.016) than those who did not. Participation in social activities was positively associated with establishing health records only in urban communities (OR 1.853, 95% CI 1.060 to 3.239), and it was positively linked to receiving health education information among those living with a higher percentage of local neighbours (OR 1.451, 95% CI 1.044 to 2.017). Conclusions: Structural social capital was related to an increased utilisation of local public health services among migrants. The findings of this study provided new evidence for the differential influences of social capital by neighbourhood characteristics in China, which suggested the importance to enhance social capital in rural/suburban communities and communities where the majority of the residents were migrants.